(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we introduce the notion of quasi statistical convergence of double sequences in the neutrosophic normed spaces mainly as a generalization of statistical convergence of double sequences. We investigate a few fundamental properties of the newly introduced notion and examine the relationship with statistical convergence of double sequences in the neutrosophic normed spaces. In the end, we introduce the concept of quasi statistical Cauchy sequence of double sequences and show that quasi statistical Cauchy sequences for double sequences are equivalent to quasi statistical convergent double sequences in the neutrosophic normed spaces.